Customer satisfaction model and organisational strategies for Land Registration and Cadastral Systems - Tuladhar, Arbind Man; Molen, Paul van der (Journal on Geoinformatics, Nepal, 2007)
Many land registration and cadastre offices have now tremendous pressures from various public and private sectors to improve their workflows of the systems for land registration and cadastral surveying including archiving historical documents of deeds/titles and maps. In this era of Information technology, the use of computers is seen as immediate solution for reengineering these systems and digital archiving. But the pressures have not only to do with the improvement of internal digital workflows and archiving but also to improve the customer satisfaction with the services and products offered by these digital systems. Since the customer satisfaction and relationship are most important, it is argued that the customer satisfaction model should be an integral part of organizational strategy model to delivery efficient and effective services and products to the customer. Customer satisfaction model normally relates to the delivering superior relative perceived value, getting substantial base in the market and gaining profitability via scale economies. Moreover, the relationships with customers are strongly dependent with the roles that both organisation and customers have to play during interaction. In this research paper, we discuss three issues on the customers and organisations relationships for the land registration and cadastral systems. First issue concentrates the elements of customer satisfaction model and second one on the perceived value. Last issue deals with how this model can be incorporated into an organisational strategy model that could be either a push strategy or a pull strategy of reengineering process.